Decoherence of the Kondo Singlet Caused by Fano Resonance (Journal of Atomic and Molecular Sciences, 2014)
We investigate the structure of an Aharonov-Bohm interferometer with aquantum dot coupling to left and right electrodes. By employing cluster expansions,the equations of motion of Green's functions are transformed into the correspondingequation of motion of connected Green's functions, which provides a truncationscheme. With this method under the Lacroix's truncation approximation, we showthat Fano resonance causes a decoherence of the Kondo singlet.